Producing a poly(N, N-dimethylaminoethyl methacrylate) nonwoven by using the blowing out method. Issue 17 (October 2016) - Zielińska, Dorota; Stawski, Dawid; Komisarczyk, Agnieszka
A poly( N, N -dimethylaminoethyl methacrylate) nonwoven was produced by the blowing out technique. The basic structural and mechanical properties of the obtained material were measured and described. It was found that the formed nonwoven has a smooth and delicate structure with quite weak mechanical properties. Its antibacterial properties against Staphylococcus aureus and Escherichia coli bacteria were shown. Some medical applications were suggested.